2003
DOI: 10.1136/ijgc-00009577-200311001-00013
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation therapy revisited: intravenous chemotherapy

Abstract: The administration of ‘consolidation’ therapy is designed to maximize the benefits achieved from primary chemotherapy, to both improve progression-free and overall survival. Paclitaxel is an excellent agent to consider for a consolidation strategy in ovarian cancer, based on its activity in the disease, its cycle-specificity, and the lack of serious cumulative toxicity (except for neuropathy). A recently reported randomized trial conducted by the South-west Oncology Group and the Gynecologic Oncology Group rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A recently reported randomized trial conducted by the South-west Oncology Group and the Gynecologic Oncology Group revealed that 12-monthly cycles of single-agent paclitaxel (175 mg/m 2 over 3 h) improves PFS, compared to 3-monthly cycles of the agent (median PFS: 28 months versus 21 months, P ¼ 0.0023, HR 2.31) (57) . However, an impact of consolidation on quality-adjusted or OS has not been demonstrated.…”
Section: Maintenance-consolidation Treatmentmentioning
confidence: 99%
“…A recently reported randomized trial conducted by the South-west Oncology Group and the Gynecologic Oncology Group revealed that 12-monthly cycles of single-agent paclitaxel (175 mg/m 2 over 3 h) improves PFS, compared to 3-monthly cycles of the agent (median PFS: 28 months versus 21 months, P ¼ 0.0023, HR 2.31) (57) . However, an impact of consolidation on quality-adjusted or OS has not been demonstrated.…”
Section: Maintenance-consolidation Treatmentmentioning
confidence: 99%